CONCEPTUAL APPROACHES TO IMPROVING CONSUMER CREDIT IN WAR CONDITIONS - Волкова, Валерія; Волкова, Неля (SWorldJournal, 2026)
The article reveals the trends in the development of consumer lending in Ukraine, threats and challenges associated with Russian aggression and directions for overcoming them by introducing innovations in the means and instruments of the lending system.